Understanding how nurses ration care. Issue 3 (11th April 2018) - Harvey, Clare Lynette; Thompson, Shona; Willis, Eileen; Meyer, Alannah; Pearson, Maria
Abstract : Purpose: The purpose of this paper is to explore how nurses make decisions to ration care or leave it undone within a clinical environment that is controlled by systems level cost containment. The authors wanted to find out what professional, personal and organisational factors contribute to that decision-making process. This work follows previous international research that explored missed nursing care using Kalisch and Williams' MISSCARE survey. Design/methodology/approach: The authors drew on the care elements used by Kalisch and Williams, asking nurses to tell us how they decided what care to leave out, the conduits for which could include delaying care during a shift, delegating care to another health professional on the same shift, handing care over to staff on the next shift or leaving care undone. Findings: The findings suggest that nurses do not readily consider their accountability when deciding what care to leave or delay, instead their priorities focus on the patient and the organisation, the outcomes for which are frequently achieved by completing work after a shift. Originality/value: The actions of nurses implicitly rationing care is largely hidden from view, the consequences for which potentially have far reaching effects to the nurses and the patients. This paper raised awareness to hidden issues facing nurses within a cycle of implicitly rationing care, caught between wanting to provide care to their patients, meeting the organisation's directives and ensuring professional safety. Rethinking how care is measured to reflect its unpredictable nature is essential.